Deploying Unmanned Surface Vehicle for Cleaning Tsunami Aftermath - Razali, Ahmad Izham (IRC, 2019)
Tsunamis are a natural disaster that contributed to marine pollution on a large scale, showed by the aftermath of the tsunami caused by the 2011 Great East Japan Earthquake. The pollutants would further be causing more severe issues to the marine biota and human. Therefore, an initiative of capturing and preventing the pollutants from drifting to open ocean where the removal process is tougher is proposed, using unmanned surface vessels (USVs).